Synthesis method and application of dual-response bimetallic nano-catalyst

By developing the bimetallic nanocatalyst CuFeMOF@GOx@Mem, the problems of low catalyst efficiency, insufficient H2O2 content and GSH overexpression were solved, and the efficacy of CDT was significantly improved, providing an efficient tumor treatment strategy.

CN119385970AInactive Publication Date: 2025-02-07SECOND AFFILIATED HOSPITAL OF COLLEGE OF MEDICINEOF XIAN JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411525498.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing cancer treatment technologies, low catalyst efficiency, insufficient H2O2 content in tumor tissues, and overexpression of glutathione (GSH) lead to poor efficacy of chemodynamic therapy (CDT).

Method used

Develop a dual-responsive bimetallic nanocatalyst CuFeMOF@GOx@Mem, which generates H2O2 in situ in the tumor through nanoenzymes, and uses red blood cell membrane modification to enhance tumor targeting capabilities, so as to realize CuFeMOF releases metal ions under acidic conditions and in GSH Convert to efficient catalyst under action.

Benefits of technology

Through the triple regulation mechanism of H2O2 self-supply, catalyst self-circulation and GSH self-elimination, the efficacy of CDT is significantly improved and the killing ability of tumors is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119385970A_ABST
    Figure CN119385970A_ABST
Patent Text Reader

Abstract

The invention relates to the field of cancer treatment, and particularly discloses a synthetic method and application of a dual-response bimetallic nano-catalyst, and the synthetic method comprises the following steps: 1, synthesizing CuFeMOF nanoparticles; (2) synthesizing CuFeMOF (at) GOx nano particles; step 3, synthesizing a CuFeMOF (at) GOx (at) Mem) nano particle structure catalyst; under the action of an erythrocyte membrane, after the CuFeMOF (at) GOx (at) Mem is accumulated in a tumor tissue, GOx catalyzes glucose to generate H2O2 and gluconic acid, the gluconic acid aggravates reduction of PH in the tissue, the CuFeMOF (at) GOx (at) Mem is further activated to release Fe < 3 + > and Cu < 2 + >, then the Fe < 3 + > and the Cu < 2 + > are converted into Fe < 2 + > and Cu < + > by GSH, and Fe < 2 + >-mediated Fenton reaction is activated; in addition, Cu < + > can further promote conversion from Fe < 3 + > to Fe < 2 + >, and the CDT (chemodynamic therapy) effect is enhanced. The capacity of continuously accumulating Fe < 2 + > and eliminating GSH is shown through the amplification effect among GSH, Fe and Cu ions. In conclusion, according to the nano system, the effect of the CDT is greatly improved through a triple regulation mechanism of H2O2 self-supply, catalyst self-circulation and GSH self-elimination, and a unique method is provided for improving the anti-tumor potential of the CDT.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cancer treatment, and in particular to a synthesis method and application of a dual-response bimetallic nanocatalyst. Background Art

[0002] Chemodynamic therapy (CDT) is a new type of tumor treatment based on reactive oxygen species (ROS), which converts H2O2 overexpressed by tumors into highly reactive ·OH through metal ions. CDT has excellent application prospects because it avoids the need for oxygen and external stimulation (sound, light, electricity) of other ROS-based therapies.

[0003] Although Fe-based materials are currently the most important catalyst for CDT, 3+ Fe 2+ The low conversion efficiency is the rate-limiting step that affects its catalytic efficiency. Previous studies have shown that the introduction of exogenous reductants (such as tannic acid) can accelerate the conversion of Fe 3+ / Fe 2+ However, due to the reducing property of tannic acid, it promotes the conversion of Fe 3+ / Fe 2+ During the conversion, it is inevitable to neutralize part of the OH. Therefore, the current research focuses on developing a strategy to improve the Fe 2+ The generation efficiency of ROS is not increased without increasing the consumption of ROS. From a thermodynamic point of view, the redox potential is lower than that of the iron ion (E0(Fe 3+ / Fe 2+ )=0.77V) such as Zn, Cu, Co and Cr, which can 3+ Converted to Fe 2+ The redox potential of Cu (E0(Cu 2+ / Cu + )=0.17V) is much lower than Fe, and also has significant biological functions and Fenton-like catalytic properties, making it an important metal for triggering anti-tumor CDT together with Fe. In addition, among many inorganic nanocatalysts, metal-organic framework materials have irreplaceable advantages, such as large surface area, good acid-responsive release performance, and high drug loading efficiency. Therefore, bimetallic metal-organic framework materials will be a promising and efficient Fenton catalyst that can realize the "self-circulation" effect of metal ions.

[0004] Upregulation of glutathione (GSH) plays a key role in enhancing cellular resistance to ROS-based therapies. Therefore, researchers have designed various approaches to inhibit the functions of various proteins involved in GSH synthesis. However, because the synthesis of GSH is regulated by multiple pathways, the efficacy of strategies that inhibit a single protein is often limited. Given the reducing properties of GSH, exogenous oxidants have the potential to directly counteract GSH. Under non-reducing conditions, metal ions exhibit high-valent states with oxidative properties, making them favorable candidates for direct elimination of GSH. At the same time, in this process, catalytically inert high-valent metal ions are reduced to catalytically efficient low-valent metal ions, which in turn trigger catalytic reactions, forming a "virtuous cycle" between eliminating GSH and generating active metal ions.

[0005] H2O2, as the main raw material of Fenton catalysis, has a very limited content in tumor tissue (20-100μM), making it difficult to trigger an effective catalytic reaction.

[0006] In summary, due to the fatal weaknesses of low catalyst efficiency, insufficient H2O2 content in tumor tissue and overexpression of GSH leading to poor efficacy of CDT, it is urgent to construct a nanocatalytic system to comprehensively improve the efficacy of CDT. Summary of the invention

[0007] To achieve the above object, the present invention provides the following technical solution: a method for synthesizing a dual-responsive bimetallic nanocatalyst, comprising:

[0008] Step 1: Synthesis of CuFeMOF nanoparticles;

[0009] Step 2: Synthesis of CuFeMOF@GOx nanoparticles;

[0010] Step 3: Synthesis of CuFeMOF@GOx@Mem nanoparticle structure catalyst.

[0011] Preferably, the method for synthesizing CuFeMOF nanoparticles is:

[0012] Mix 0.25 mL of FeCl3-6H2O (100 mM) in DMF with deionized water (2 mL) and stir at 50 °C for 15 min;

[0013] Then, Cu(NO3)2-3H2O (100 mM) DMF solution and H2BDC DMF solution were slowly added at a rate of 0.44 mL / h and 0.5 mL / h, respectively. After 4 hours of reaction, the solution turned flesh-pink and was washed three times with DMF and water, respectively, to obtain CuFeMOF nanoparticles. Single metal MOFs (CuMOF and FeMOF) were synthesized by similar methods as control materials.

[0014] Preferably, the method for synthesizing CuFeMOF@GOx nanoparticles is:

[0015] The synthesized CuFeMOF nanoparticles (1 mg) were dispersed in 4 mL of H2O, and then GOx aqueous solution (100 μg / mL, 1 mL) was added and stirred at 4 °C for 4 h;

[0016] Finally, the precipitate was collected by centrifugation and washed with water three times to remove free GOx and obtain pure CuFeMOF@GOx nanoparticles.

[0017] Preferably, the method for synthesizing CuFeMOF@GOx@Mem nanoparticles is:

[0018] First, whole blood of C57 mice was collected by eye bleeding;

[0019] Subsequently, the samples were centrifuged at 3000 rpm for 5 min at 4 °C to further obtain red blood cells;

[0020] Afterwards, the erythrocytes were resuspended in 0.25 mM EDTA solution to induce rupture, and the erythrocyte membranes were collected by centrifugation at 14,000 g for 35 min. The hypotonic rupture and centrifugation operations were repeated until the upper solution was colorless, and finally the erythrocyte membranes were lyophilized;

[0021] The red blood cell membrane solution (1 mg / mL, 1 mL) was mixed with the CuFeMOF@GOx solution (1 mg / mL, 1 mL) and co-extruded 15 times through a polycarbonate porous membrane (800 nm, 400 nm) using an Avanti mini extruder to obtain CuFeMOF@GOx@Mem nanoparticles.

[0022] Preferably, a CuFeMOF@GOx@Mem nanoparticle structure catalyst prepared by any of the synthesis methods described above.

[0023] Preferably, a catalytic CuFeMOF@GOx@Mem is used for the treatment of cancer, using the CuFeMOF@GOx@Mem nanoparticle structure catalyst as described above, with the help of the red blood cell membrane, after CuFeMOF@GOx@Mem accumulates in tumor tissue, GOx catalyzes glucose to generate H2O2 and gluconic acid, and gluconic acid further causes the pH in the tissue to decrease, which activates CuFeMOF@GOx@Mem to release Fe 3+ and Cu 2+ , which is subsequently converted by GSH into Fe 2+ and Cu + , activate Fe 2+ mediated Fenton reaction; in addition, Cu + It can also further promote Fe 3+ To Fe2+ The conversion of Fe 2+ The generated cycle enhances the cancer therapeutic ability of CuFeMOF@GOx@Mem.

[0024] The present invention has at least the following beneficial effects:

[0025] 1. To address the problem of lack of H2O2 in tumor tissue, a more targeted solution has been proposed, which uses nanozymes to generate H2O2 in situ from glucose or lactate that is rich in tumors. 2, Specifically, glucose oxidase (GOx) is an important enzyme in the field of tumor diagnosis and treatment. It can not only produce a large amount of H2O2, but also destroy the glucose metabolism of tumors, inducing energy deprivation and starvation therapy. On this basis, a pH / GSH dual-responsive bimetallic nanocatalytic system (CuFeMOF@GOx@Mem) was designed to comprehensively promote the ability of chemokinetic therapy of tumors by simultaneously regulating three factors that affect CDT efficiency. Then, CuFeMOF releases Fe under acidic conditions. 3+ and Cu 2+ , and then converted to Fe under the reduction of GSH 2+ and Cu + , which rapidly triggered the 2+ mediated Fenton reaction.

[0026] 2. CuFeMOF@GOx@Mem was synthesized by further modifying the red blood cell membrane of GOx-loaded iron-copper bimetallic MOFs. The addition of red blood cell membrane prolongs the circulation time of the nanosystem in the blood, thereby improving the tumor targeting enrichment ability of the nanosystem. After CuFeMOF@GOx@Mem is enriched in tumor tissue, GOx first catalyzes glucose to produce H2O2 and gluconic acid. This process not only provides the raw material H2O2 for Fenton catalysis, but also creates a suitable acidic environment for CDT to occur;

[0027] 3. The nanosystem demonstrated continuous accumulation of Fe through a cyclic amplification effect between GSH, Fe, and Cu ions. 2+ and the ability to eliminate GSH for efficient Fenton catalysis. In summary, this nanosystem greatly improves the efficacy of CDT through the triple regulatory mechanism of H2O2 self-supply, catalyst self-circulation, and GSH self-elimination, providing a unique approach to enhance the anti-tumor potential of CDT. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A- Figure 1H is a characterization diagram of CuFeMOF@GOx@Mem of the present invention, wherein 1A is a scanning electron microscope (SEM) image of CuFeMOF@GOx, wherein 1B and 1C are transmission electron microscope (TEM) images of CuFeMOF@GOx, wherein 1D is a TEM element distribution diagram of CuFeMOF@GOx and 1E is a corresponding element ratio, wherein 1F (1) is a red blood cell, (2) is a red blood cell membrane, (3) is CuFeMOF@GOx, and (4) is a SDS-polyacrylamide gel electrophoresis (SDS-PAGE) protein analysis diagram of CuFeMOF@GOx@Mem, wherein 1G is a particle size distribution and 1 Hz eta potential diagram of CuFeMOF@GOx@Mem;

[0029] Figure 2 A- Figure 2 L is a verification diagram of the catalytic ability of CuFeMOF@GOx of the present invention, wherein 2A is the consumption of glucose in PBS (pH7.4) containing glucose at different time points, wherein 2B is the generation of H2O2 in PBS containing glucose at different time points, wherein 2C is the pH change in PBS containing glucose at different time points, wherein 2D is the release of iron and copper ions by CuFeMOF over time under different pH conditions, wherein 2E is the change in TMB absorbance of CuFeMOF with different GSH concentrations in a buffer (pH5.5) containing H2O2 (500μM), wherein 2F is the TMB absorbance of CuFeMOF in a buffer (pH5.5) containing H2O2 (500μM) and GSH (1mM) at different time points , where 2G is the change of TMB absorbance of CuFeMOF with different pH values ​​under the conditions of H2O2 (500 μM) and GSH (1 mM), where 2H is the change of TMB absorbance of different materials in a buffer (pH = 5.5) containing H2O2 (500 μM) and GSH (1 mM) at different time points, where 2 is the MB degradation of ICuFeMOF in a buffer (pH 5.5) containing H2O2 (500 μM) and GSH (1 mM) at different time points, where 2J is the single metal and bimetallic MOF in PBS (pH 7.4) containing glucose at different glucose concentrations, where 2K is at different time points, where 2L is the TMB absorbance at the same GOx concentration;

[0030] Figure 3 A- Figure 3 C is the analysis of nanomedicine on mice, 3A is the cytotoxicity of different nanomedicines on Hepa1-6 cells, 3B is the cytotoxicity of FeMOF, CuMOF and CuFeMOF on Hepa1-6 cells in the absence of H2O2 and C with H2O2;

[0031] Figure 4 A- Figure 4 C is a fluorescence image, where 4A is an in vivo fluorescence image of Hepa1-6 tumor-bearing mice after intravenous injection of CuFeMOF@GOx@Mem and IR780, where 4B is an in vitro fluorescence image of major organs and tumors, where 4C is the corresponding average fluorescence intensity value;

[0032] Figure 5 A- Figure 5 F is the in vivo antitumor efficiency of CuFeMOF@GOx@Mem, where 5A is a schematic diagram of the establishment of the Hepa1-6 tumor-bearing mouse model and the treatment schedule,

[0033] 5B is the anti-tumor effect of different drugs on Hepa1-6 tumor-bearing mice (n=6).

[0034] 5C is the average tumor weight of mice after treatment.

[0035] 5D is an in vitro photograph of tumor tissue.

[0036] Among them, 5E is

[0037] G1: PBS, G2: GOx, G3: FeMOF, G4: CuMOF, G5: CuFeMOF, G6: CuFeMOF@GOx, G7: CuFeMOF@GOx@Mem, H&E staining of tumor tissues after 14 days of treatment,

[0038] Among them, 5F is the immunofluorescence staining image of Caspase-3. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example

[0041] See also Figure 1 A- Figure 1 H to Figure 5 A- Figure 5F, the present invention provides materials, Cu(NO3)2-3H2O, FeCl3-6H2O, terephthalic acid (H2BDC) and glucose were purchased from Aladdin Reagent Co., Ltd. (China). Glucose oxidase (GOx) was purchased from Shanghai Yuanye Biotechnology Co., Ltd. Hydrogen peroxide detection kit, calcein-AM, JC-1 probe, cell apoptosis and necrosis detection kit (Hoechst33342 and PI double staining), cell membrane and cell membrane protein extraction kit were purchased from China Institute of Biotechnology. Reactive oxygen detection kit (DHE) was purchased from Shanghai Yubo Biotechnology Co., Ltd. Unless otherwise stated, all other materials were used directly as is.

[0042] instrument

[0043] TEM images were obtained on a Talos F200i (Thermo Fisher Scientific, USA) at 200 kV. Hydrodynamic size and zeta potential were determined by dynamic light scattering (DLS) on a Litesizer 500 instrument. UV-visible spectrophotometer (Lambda Bio 40) was used for measurement. In vivo imaging experiments were performed using an in vivo imaging system (IVIS) (Perkin Elmer). Metal release was determined by ICP-AES (Agilent 5110).

[0044] Synthesis of CuFeMOF@GOx@Mem nanoparticles

[0045] Synthesis of CuFeMOF nanoparticles: First, 0.25mL of FeCl3-6H2O (100mM) DMF solution was mixed with deionized water (2mL) and stirred at 50°C for 15 minutes. Then, Cu(NO3)2-3H2O (100mM) DMF solution and H2BDC DMF solution were slowly added at a rate of 0.44mL / h and 0.5mL / h, respectively. After 4 hours of reaction, the solution turned into a flesh-pink color, and then washed with DMF and water for 3 times to obtain CuFeMOF nanoparticles. Single metal MOFs (CuMOF and FeMOF) were synthesized in a similar way as control materials.

[0046] Synthesis of CuFeMOF@GOx nanoparticles: The synthesized CuFeMOF nanoparticles (1 mg) were dispersed in 4 mL of H2O, and then GOx aqueous solution (100 μg / mL, 1 mL) was added and stirred at 4 °C for 4 h. Finally, the precipitate was collected by centrifugation and washed with water three times to remove free GOx and obtain pure CuFeMOF@GOx nanoparticles.

[0047] Synthesis of CuFeMOF@GOx@Mem nanoparticles: Extraction of red blood cell membrane: First, whole blood of C57 mice was collected by eye sampling, and then centrifuged at 3000rpm for 5 minutes at 4°C to further obtain red blood cells. The red blood cells were then resuspended in 0.25mM EDTA solution to induce rupture, and then the red blood cell membranes were collected by centrifugation at 14000g for 35 minutes. The hypotonic rupture and centrifugation operations were repeated until the upper solution was colorless, and finally the red blood cell membranes were lyophilized.

[0048] The red blood cell membrane solution (1 mg / mL, 1 mL) was mixed with the CuFeMOF@GOx solution (1 mg / mL, 1 mL) and co-extruded 15 times through a polycarbonate porous membrane (800 nm, 400 nm) using an Avanti mini extruder to obtain CuFeMOF@GOx@Mem nanoparticles.

[0049] H2O2 generation

[0050] The ability of CuFeMOF@GOx to catalyze glucose to produce H2O2 was tested by the hydrogen peroxide detection kit. CuFeMOF@GOx and CuFeMOF (200 μg / mL) were dispersed in glucose solution (1 mg / mL), respectively. Then, the supernatant was collected by centrifugation at a given time point, and the H2O2 concentration was further detected using the kit. Each sample was tested three times.

[0051] Glucose testing

[0052] The classic DNS method was used to detect the glucose consumption capacity of CuFeMOF@GOx. Specifically, the test solution (1 mL) was mixed with water (1 mL) and DNS reagent (3 mL), and then incubated at 100°C for 5 minutes. Finally, the absorption of the mixture at a wavelength of 532 nm was detected using a multifunctional microplate reader. In the solution experiment, the DNS reagent was used to determine the glucose content of the glucose solution (1 mg / mL) containing CuFeMOF@GOx (200 μg / mL) at different time points. In the cell experiment, the cell culture medium after different sample treatments was collected to detect the glucose consumption capacity at the cellular level.

[0053] pH change detection

[0054] CuFeMOF@GOx and CuFeMOF (200 μg / mL) were dispersed in PBS (pH=7.4) containing glucose (1 mg / mL), respectively. The pH value of PBS was then recorded at different time intervals using a pH meter.

[0055] OH generation

[0056] The nanoparticles under different conditions were tested by methylene blue (MB) degradation and TMB coloring experiments. 10μg / mL TMB, 400μM H2O2, and 200μg / mL CuFeMOF were dispersed in buffers with different pH values ​​and GSH concentrations, respectively. Then, the UV-visible absorption of TMB at a wavelength of 652nm was measured at different time points to verify the effects of GSH and pH on the generation of ·OH from CuFeMOF. In addition, methylene blue degradation experiments were also used to further verify the ability of monometallic MOF and bimetallic MOF to produce ·OH under the same reaction conditions and the same concentrations of copper ions (3.5μg / mL) and iron ions (16.1μg / mL).

[0057] Subsequently, in order to further prove the cascade catalytic effect initiated by GOx, the TMB (10 μg / mL) colorimetric method was used to detect the production of ·OH by CuFeMOF@GOx (200 μg / mL) in PBS containing different concentrations of glucose. In addition, the same method was used to detect the production of ·OH by single metal MOF (FeMOF, CuMOF) and bimetallic MOF (CuFeMOF@GOx) in the presence of equal concentrations of GOx (2 μg / mL), copper ions (3.5 μg / mL) or iron ions (16.1 μg / mL).

[0058] Metal ion release and valence state analysis

[0059] Total release of metal ions: 1,10-phenanthroline and 2,9-dimethyl-1,10-phenanthroline were used as detection probes for iron and copper ions, respectively, to measure the metal ions released from nanoparticles under different pH conditions. CuFeMOF nanoparticles (500 μg / mL) were dispersed in PBS with different pH values ​​(7.4 or 5.5) and stirred in a horizontal shaker at 37 °C (100 rpm). At a given time point, the PBS containing the material was centrifuged, 500 μL of the supernatant was removed, and then 500 μL of fresh buffer of the corresponding pH value was supplemented. Then, ascorbic acid was added to the supernatant for 15 minutes to reduce all metal ions to metastable states, and 1,10-phenanthroline and 2,9-dimethyl-1,10-phenanthroline were used as indicators to detect UV absorption at 510 nm and 405 nm, respectively, to determine the concentrations of iron and copper ions in the system. Finally, the release of iron and copper ions was calculated according to the corresponding standard curves. The total contents of iron and copper in CuFeMOF were determined by ICP method.

[0060] Fe 2+ Detection: The supernatant without ascorbic acid was subjected to UV-visible absorption detection in the same way to determine the Fe 2+ content.

[0061] GSH elimination assay

[0062] In the solution experiment, Ellman's reagent was used to detect GSH-containing solutions treated with different samples. The supernatant (50 μL) at different time points was added to 100 μL Ellman's reagent (1.5 mg / mL), and the UV-visible absorbance (405 nm) was further measured using a multi-function microplate reader. Cellular GSH detection: Hepa1-6 cells were seeded on a 6-well plate, the samples were added and incubated for 4 hours, and then the cells were lysed with Triton-X-100 (200 μL, 4%), and the lysate was collected and centrifuged. Finally, the supernatant was further measured with Ellman's reagent in the same way as the liquid test.

[0063] Cell culture

[0064] Mouse hepatoma cells (Hepa1-6) were cultured in DMEM medium containing fetal bovine serum (FBS, 10%) and antibiotics (penicillin-streptomycin, 10,000 U / mL, 1%) at 37°C in a 5% CO2 humidified environment.

[0065] Cytotoxicity assay

[0066] The MTT method was used to detect the cytotoxicity of CuFeMOF@GOx on Hepa1-6 cells. Hepa1-6 cells were cultured in a 96-well plate for 24 hours, and then the old culture medium was replaced with fresh culture medium containing samples of different concentration gradients. After another 4 hours of culture, the culture medium was replaced with 150 μL of DMSO to completely dissolve the formazan. Finally, the UV-visible absorbance at a wavelength of 570 nm was recorded using a multifunctional microplate reader. The calculation formula for cell viability (%) is (OD570 (sample) / OD570 (control)) X 100%. OD570 (sample) represents the wells treated with the material, and OD570 (control) represents the wells that have not been treated.

[0067] In vivo tumor targeting studies

[0068] All experiments on live animals were performed in accordance with the protocols of the Animal Care and Use Committee of the Animal Experiment Center of Xi'an Jiaotong University (Xi'an, China).

[0069] When female C57 mice were about 7 weeks old, hepa1-6 cells were subcutaneously injected into the right dorsal flank to establish a tumor mouse model. 3At the same time, IR780-labeled CuFeMOF@GOx@Mem and CuFeMOF@GOx were injected into the tail vein, respectively. Then, the mice were photographed at given time points using the small animal in vivo imaging system (IVIS). At the last time point, the mice were euthanized, and tumor tissues and other major organs were collected and photographed to observe the distribution of CuFeMOF@GOx@Mem in the body.

[0070] In vivo antitumor effect

[0071] After the Hepa1-6 tumor mouse model was established, when the tumor volume reached 100 mm 3 The mice were randomly divided into 7 groups (6 mice in each group). Then, 1) PBS, 2) GOx, 3) FeMOF, 4) CuMOF, 5) CuFeMOF, 6) CuFeMOF@GOx, and 7) CuFeMOF@GOx@@Mem were injected through the tail vein on the 1st, 3rd, and 6th days, respectively. During the treatment period, the weight of the mice, the length and width of the tumor were measured and recorded every day. The tumor volume (V) was calculated as width 2 X length / 2, relative tumor volume (%) was defined as V / V0, where V0 was the tumor volume on day 1. All mice were killed after treatment, and tumor tissues and other major organs were collected for H&E and Ki67 / caspase-3 immunofluorescence staining to further evaluate the anti-tumor mechanism at the molecular level.

[0072] Results and Discussion

[0073] Preparation and characterization of CuFeMOF@GOx@Mem

[0074] CuFeMOF was synthesized by additional doping with copper ions according to the synthesis method of MIL-101(Fe) in the reference literature. Their dispersion and morphology were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 A-1C). As can be seen from the figure, CuFeMOF has a uniform distribution morphology of about 120nm. In order to more intuitively and clearly demonstrate the successful preparation of bimetallic MOF. We also performed TEM elemental analysis on CuFeMOF, and the results showed that there are iron and copper elements in the material ( Figure 1 D and 1E), which fully demonstrated the successful preparation of bimetallic MOF. Subsequently, CuFeMOF@GOx was further obtained through the electrostatic force between CuFeMOF (positive charge) and GOx (negative charge). The loading efficiency of GOx was measured by BCA protein detection method, which was about 1% (mass ratio). In addition, the total iron ion content measured by ICP-AES was about 8.0%, and the total copper ion content was about 1.8%.

[0075] In addition, red blood cell membranes were collected based on our previous work. Then, the membranes and CuFeMOF@GOx were mixed in equal proportions. Finally, the mixture was extruded through an Avanti mini extruder to obtain CuFeMOF@GOx@Mem. Afterwards, to prove that the membrane coating was successful, the samples were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The protein profile of CuFeMOF@GOx@Mem was highly consistent with that of red blood cells and membranes, indicating that the membrane coating was successful ( Figure 1 F). In addition, the size of the nanoparticles varies from Increase to ( Figure 1 G), zeta potential from Down to ( Figure 1 H), which are all attributed to the modification of CuFeMOF by GOx and the negatively charged membrane, further proving the successful preparation of CuFeMOF@GOx@Mem.

[0076] Cascade catalytic ability of CuFeMOF@GOx

[0077] The ability of GOx to consume glucose to produce H2O2 and gluconic acid is its main mechanism of action. Based on this, we used glucose consumption, H2O2 generation and pH reduction experiments to evaluate the catalytic activity of GOx in CuFeMOF@GOx. First, the DNS method was used to determine the glucose content. Figure 2 As shown in A, the glucose concentration in the glucose solution containing CuFeMOF@GOx gradually decreased over time. In addition, the generated H2O2 detected by the H2O2 detection kit gradually increased with the extension of the reaction time ( Figure 2 B), providing sufficient raw materials for subsequent metal ion-mediated catalytic reactions. In addition, over time, CuFeMOF@GOx continuously reduces the pH value of PBS containing glucose and eventually stabilizes at around 3.8 ( Figure 2 C). All these results indicate that the loading and modification of GOx by materials do not affect the catalytic activity of GOx. More importantly, the generation of H2O2 and the ability to reduce pH in this process provide a guarantee for the promotion of metal ion-mediated catalysis.

[0078] Subsequently, considering the ability of MIL-101 to release metal ions under acidic conditions, we used the classic 1,10-phenanthroline (iron detection) and 2,9-dimethyl-1,10-phenanthroline (copper detection) methods to detect the ability of CuFeMOF@GOx to release metal ions under acidic conditions to evaluate its acid-responsive performance. Figure 2D It can be seen that under acidic pH conditions, the release of both iron and copper ions increases with time. After 12 hours, the release rate reaches about 80%, close to the maximum value. In contrast, at a pH of 7.4, CuFeMOF@GOx releases almost no iron ions and only a small amount of copper ions. These results demonstrate the acid-responsive properties of CuFeMOF@GOx and also indicate that acid is a necessary condition for initiating subsequent catalytic reactions.

[0079] We then investigated the ability of the bimetallic MOF to generate ·OH. We found that in the absence of GSH, no ·OH was detected in an acidic buffer containing H2O2. In contrast, under the same conditions in the presence of GSH, ·OH was detected, and the level of ·OH generated increased with increasing GSH concentration ( Figure 2 E). In addition, under acidic conditions in the presence of GSH, the CuFeMOF-mediated catalysis revealed that the amount of ·OH generated from H2O2 tended to increase with time ( Figure 2 F) From Figure 2 G shows that the generation of ·OH can only be detected under acidic conditions. These results suggest that the key factors initiating metal ion-mediated catalytic reactions are not only acidity but also GSH. More interestingly, Figure 2 It can be observed from H and 2I that under the same conditions, CuFeMOF has the strongest color development ability in TMB and the strongest fading ability in MB, which indicates that compared with single metal MOFs (FeMOF and CuMOF), bimetallic MOFs exhibit the best ·OH generation ability under acidic conditions in the presence of GSH.

[0080] After successfully verifying the catalytic activity of GOx, the acid-responsive release of metal ions, and the generation of ·OH promoted by GSH, the ability of CuFeMOF@GOx to generate ·OH in PBS containing glucose was further investigated. Figure 2 J) and time ( Figure 2 With the increase of K, the generated ·OH gradually increases, which indicates that CuFeMOF@GOx can achieve enhanced CDT through the cascade catalytic reaction mediated by GOx metal. In addition, in the presence of the same concentration of GOx, the -OH generation ability of CuFeMOF is still much higher than that of FeMOF and CuMOF ( Figure 2 L).

[0081] The above results can prove the following two conclusions: 1) acidic environment and GSH are two necessary factors to trigger the bimetallic-mediated ·OH generation; 2) in the presence of GSH, the catalytic ability of bimetallic MOF is better than that of monometallic MOF.

[0082] In vitro tumor cell killing ability of CuFeMOF@GOx

[0083] After verifying the efficient OH generation properties of CuFeMOF@GOx, we further studied its killing effect on tumor cells ( Figure 3 A). Cells treated with GOx alone caused some cell damage due to its ability to consume glucose, resulting in a cell starvation effect. In addition, without the addition of H2O2, cells treated with CuFeMOF showed little killing effect, indicating that insufficient H2O2 in the cells could not trigger the metal ion-mediated Fenton catalysis. More importantly, at the same GOx concentration, the cell killing effect of CuFeMOF@GOx was significantly stronger than that of FeMOF@GOx, showing the best cell killing effect. This phenomenon is mainly attributed to the GOx-mediated H2O2 generation and the Cu ion-enhanced Fe 3+ / Fe 2+ To further confirm the killing mechanism of the materials on cells, we also conducted more direct experiments to prove this point. First, in the absence of additional H2O2, the cell-killing effects of FeMOF, CuMOF or CuFeMOF were very limited, which confirmed that insufficient H2O2 in cells could not trigger an effective Fenton reaction ( Figure 3 B). However, when H2O2 was added, CuFeMOF showed a significantly stronger tumor killing effect than single metal MOF, which was mainly attributed to the Cu-mediated effect of improving ·OH generation ( Figure 3 C). In addition, due to the low content of Cu, CuMOF hardly causes cell death and cannot achieve an effective tumorigenic effect.

[0084] In vivo biodistribution of CuFeMOF@GOx@Mem

[0085] The distribution of nanomaterials in vitro directly affects their anti-tumor efficacy and biosafety. Considering the biological barrier problem of nanomedicine delivery in vivo, we used red blood cell membranes to wrap CuFeMOF@GOx (CuFeMOF@GOx@Mem) to improve the circulation time and tumor enrichment efficiency of nanomaterials in vivo. We constructed a subcutaneous tumor mouse model and performed in vivo fluorescence imaging using the IVIS imaging system to record the fluorescence distribution at different time points. Figure 4 As shown in A, the fluorescence intensity of the tumor site of mice injected with IR780-labeled CuFeMOF@GOx@Mem increased over time and reached maximum enrichment at 12 hours. This is mainly because the presence of the erythrocyte membrane envelope reduces the phagocytosis of nanomaterials by macrophages and prolongs the circulation time of nanomaterials in the blood, thereby increasing the enrichment of nanomaterials in the tumor site. After 48 hours, tumor tissues and major organs were collected for further imaging. Figure 4 As can be seen in B and 4C, the tumor tissues of mice treated with CuFeMOF@GOx@Mem showed stronger fluorescence, which again demonstrated its excellent tumor targeting ability. On the other hand, the lungs of mice treated with IR780 showed stronger fluorescence, which to some extent proved the safety of the material for in vivo application.

[0086] In vivo antitumor ability of CuFeMOF@GOx@Mem

[0087] After verifying that CuFeMOF@GOx@Mem has good tumor targeting ability, its in vivo anti-tumor efficacy was further evaluated. Specifically, when the tumor volume of tumor mice reached 100mm 3 The mice were randomly divided into 7 groups (6 mice in each group). Then, the mice were injected with PBS, GOx, FeMOF, CuMOF, CuFeMOF, CuFeMOF@GOx and CuFeMOF@GOx@Mem via tail vein. Figure 5 A) The anti-tumor effect was evaluated by measuring the tumor size every day and calculating the change in tumor volume in mice. Figure 5 As can be seen in B, the tumor growth of mice treated with FeMOF was slightly inhibited, which is due to the fact that FeMOF catalyzes the in situ H2O2 in the tumor tissue to generate ·OH, thereby killing tumor cells. On the other hand, CuMOF has no inhibitory effect on tumor growth due to its low copper ion content. Compared with FeMOF and CuMOF, CuFeMOF has a better inhibitory effect on tumor growth, which is due to the copper ion-assisted acceleration of Fe 3+ / Fe 2+ The conversion of ·OH increased the production of ·OH, thereby improving the anti-tumor effect. In addition, the tumor growth inhibition effect of mice treated with CuFeMOF@GOx was stronger than that of mice treated with CuFeMOF, indicating that GOx intervened in glucose metabolism to produce H2O2, providing more sufficient Fenton catalytic raw materials, thereby enhancing the ·OH-mediated tumor killing effect. Among all groups, CuFeMOF@GOx@Mem had the strongest inhibitory effect on tumor growth, which was not only due to the addition of Cu and GOx, but also due to the membrane modification that enhanced the enrichment of nanodrugs at the tumor site. After the treatment, the tumor tissues of mice in each group were collected for photographing and weighing. Figure 5 As can be seen in C and 5D, the tumor size and weight of mice treated with CuFeMOF were the smallest, further confirming its excellent anti-tumor ability. In addition, we further evaluated the killing effect of these materials on tumor cells at the cellular level through hematoxylin-eosin (H&E) staining analysis. Figure 5As shown in Figure E, consistent with the in vivo anti-tumor results, it can be seen that the number of residual tumor cells in the mouse tumor tissue treated with CuFeMOF@GOx@Mem in the H&E sections is the least. At the same time, caspase3 immunofluorescence staining showed the strongest green fluorescence, indicating the weakest cell proliferation and the most cell death, further confirming that CuFeMOF@GOx@Mem has the most excellent anti-tumor effect at the cellular level ( Figure 5 F).

[0088] in conclusion

[0089] In summary, the bimetallic nanocatalytic system (CuFeMOF@GOx@Mem) developed in this paper achieved comprehensive enhancement of tumor CDT.

[0090] First, wrapping in the red blood cell membrane enhances the material's tumor accumulation ability.

[0091] Secondly, GOx in the material can produce H2O2 and gluconic acid in situ, which not only provides the raw materials required for Fenton reaction catalysis, but also creates acidic conditions for initiating Fe-mediated catalysis.

[0092] Third, and most importantly, we systematically explored the potential mechanism of bimetallic MOFs in improving CDT efficiency. The experimental results show that bimetallic MOFs greatly improve Fe 3+ / Fe 2+ conversion and GSH elimination efficiency, which indicates that the doping of Cu ions plays a very critical role in constructing an effective nanocatalytic system.

[0093] Ultimately, through the efficient synergistic effect of each component in CuFeMOF@GOx@Mem, the three major limiting factors of CDT (low catalyst efficiency, insufficient H2O2, and overexpression of GSH) were simultaneously solved, ultimately achieving a comprehensive improvement in CDT.

[0094] This nanocatalytic system with triple enhancement effects provides a new strategy to expand the further application of CDT.

[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0096] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for synthesizing a dual-responsive bimetallic nanocatalyst, characterized in that: Step 1: Synthesis of CuFeMOF nanoparticles; Step 2: Synthesis of CuFeMOF@GOx nanoparticles; Step 3: Synthesis of CuFeMOF@GOx@Mem nanoparticle structure catalyst.

2. The method for synthesizing a dual-responsive bimetallic nanocatalyst according to claim 1, characterized in that: The method for synthesizing CuFeMOF nanoparticles is: Mix 0.25 mL of FeCl3-6H2O (100 mM) in DMF with deionized water (2 mL) and stir at 50 °C for 15 min; Then, Cu(NO3)2-3H2O (100 mM) DMF solution and H2BDC DMF solution were slowly added at a rate of 0.44 mL / h and 0.5 mL / h, respectively. After 4 hours of reaction, the solution turned flesh-pink and was washed three times with DMF and water, respectively, to obtain CuFeMOF nanoparticles. Single metal MOFs (CuMOF and FeMOF) were synthesized by similar methods as control materials.

3. The method for synthesizing a dual-responsive bimetallic nanocatalyst according to claim 1, characterized in that: The method for synthesizing CuFeMOF@GOx nanoparticles is: The synthesized CuFeMOF nanoparticles (1 mg) were dispersed in 4 mL of H2O, and then GOx aqueous solution (100 μg / mL, 1 mL) was added and stirred at 4 °C for 4 h; Finally, the precipitate was collected by centrifugation and washed with water three times to remove free GOx and obtain pure CuFeMOF@GOx nanoparticles.

4. The method for synthesizing a dual-responsive bimetallic nanocatalyst according to claim 1, characterized in that: The method for synthesizing CuFeMOF@GOx@Mem nanoparticles is: First, whole blood of C57 mice was collected by eye bleeding; Subsequently, the samples were centrifuged at 3000 rpm for 5 min at 4 °C to further obtain red blood cells; Afterwards, the erythrocytes were resuspended in 0.25 mM EDTA solution to induce rupture, and the erythrocyte membranes were collected by centrifugation at 14,000 g for 35 min. The hypotonic rupture and centrifugation operations were repeated until the upper solution was colorless, and finally the erythrocyte membranes were lyophilized; The red blood cell membrane solution (1 mg / mL, 1 mL) was mixed with the CuFeMOF@GOx solution (1 mg / mL, 1 mL) and co-extruded 15 times through a polycarbonate porous membrane (800 nm, 400 nm) using an Avanti mini extruder to obtain CuFeMOF@GOx@Mem nanoparticles.

5. A CuFeMOF@GOx@Mem nanoparticle structure catalyst prepared by the synthesis method according to any one of claims 1 to 4.

6. A catalytic CuFeMOF@GOx@Mem for the treatment of cancer, using the CuFeMOF@GOx@Mem nanoparticle structure catalyst as claimed in claim 5, with the help of the red blood cell membrane, after CuFeMOF@GOx@Mem accumulates in tumor tissue, GOx catalyzes glucose to produce H2O2 and gluconic acid, and gluconic acid further causes the pH in the tissue to decrease, which activates CuFeMOF@GOx@Mem to release Fe 3+ and Cu 2+ , which is subsequently converted by GSH into Fe 2+ and Cu + , activate Fe 2+ mediated Fenton reaction; in addition, Cu + It can also further promote Fe 3+ To Fe 2+ The conversion of Fe 2+ The generated cycle enhances the cancer therapeutic ability of CuFeMOF@GOx@Mem.

Citation Information

Patent Citations

  • Nano catalyst for tumor treatment, and preparation method and application thereof

    CN110974978A

  • Porphyrin-based metal organic framework nano-carrier with sonodynamic combined starvation therapy anti-tumor function and preparation method of porphyrin-based metal organic framework nano-carrier

    CN113117079A

  • Preparation method and application of glucose oxidase modified iron-based metal organic framework nano drug delivery system

    CN114177311A